(untitled) (Lex localis - Journal of Local Self-Government, 2024)
Urban–upland systems in tropical cities face compounding hazards—flooding, landslides, heat stress, and seasonal water scarcity—whose intensity is increasing under climate change. This article analyzes how forest governance can function as ecosystem-based infrastructure for climate resilience in Zamboanga City, Philippines, an urban jurisdiction where forestlands dominate the territory and upstream ecosystem services shape downstream water security and disaster risk. Methods combine satellite-based forest-cover change assessment using Landsat imagery (2000–2022) with a governance and community strategy synthesis based on documentary review and 32 key informant interviews with Department of Environment and Natural Resources personnel, city planners, barangay officials, people’s organizations, and Indigenous representatives. Remote-sensing results are validated using 250 ground-truth points and interpreted by governance regime (protected areas, community-based forest management sites, barangay initiatives, and unmanaged forestlands). Findings show heterogeneous forest trajectories by regime. Protected areas remain broadly stable. Community-based forest management sites register positive net canopy change, including an estimated 2–3% increase after 2016 associated with tenure security, reforestation, and sustained community patrolling. Barangay-led initiatives generate localized gains (≈1%) along riparian corridors and degraded slopes, alongside reported declines in sediment loads in monitored streams that support flood mitigation and water quality. Unmanaged forestlands exhibit higher loss rates and weaker recovery, reflecting tenure uncertainty, financing gaps, and limited enforcement reach. The analysis identifies practical integration pathways: embedding forest and watershed indicators in land-use, disaster risk, and water-supply planning; formalizing inter-agency coordination through joint enforcement and interoperable monitoring; and coupling restoration with livelihood portfolios (agroforestry and non-timber forest products) to sustain participation. The case suggests that durable climate resilience emerges from reinforcing feedback loops linking institutional coherence, community agency, and measurable forest recovery at the urban–upland interface. For policymakers, the findings prioritize tenure consolidation, maintenance finance, and spatial targeting of critical watersheds, offering a replicable template for cities across Mindanao and Southeast Asia.